Metadata as a machine for feeling in Germaine Greer's archive. Issue 2 (4th May 2019) - Weber, Millicent; Buchanan, Rachel
ABSTRACT: What happens when a human coder meets a machine one? This article explores this question with reference to the archive of Professor Germaine Greer: Australian-born feminist, performer, scholar, and professional controversialist. It does so by staging two very different data encounters with the 70, 000-word finding aid for the print journalism series, a key component of Greer's archive. The first encounter is archivist's creation of the finding aid; the second, archivist and literary scholar's interpretation of this archival metadata using sentiment analysis. Interrogating these activities side-by-side opens up a productive middle ground between humanities scholars and computer technicians, between historians and archivists, between the hand made and the machine made. This article argues that sentiment analysis offers a new and highly productive method of interrogating archival metadata, and that, as a method which privileges emotive understandings of content, it is particularly appropriate to the study of feminist archives like Greer's. It also argues that these kinds of detailed finding aids are new datasets that reward analysis in their own right, and particularly when considered in dialogue with—rather than simply used as straightforward navigational tools for—the 'original' archival content.